Ownership Structure, Company Size, and Size of the Board of Commissioners on Risk Management Disclosure - Indah Maulian Nur Ikhsan; Amalia Nur Patimah; Tri Neliana (Indonesian Journal of Advanced Research, 2024)
This study aims to provide empirical evidence regarding risk management disclosure through the perspective of shareholders, company size and board of commissioners. The measurement of the dependent variable, namely risk management disclosure in this study, is calculated using the total score of disclosure items based on the ISO:31000 dimension, including 5 dimensions, namely mandate and commitment, framework planning, risk management implementation, monitoring and continuous improvement according to ISO:31000 component standards. The sample used in this study is mining companies listed on the Indonesia Stock Exchange in 2019-2022. The sample was chosen using the purposive sampling technique, which took into account information availability and compliance with predetermined criteria. 21 companies were chosen after 84 observation data points were analyzed. The test on the hypothesis uses Multiple Linear RegressionThe study of this sample's data reveals that the degree of risk management disclosure is influenced by the factors of management ownership, firm size, and board of commissioners. Meanwhile, the variables of public ownership and foreign ownership have no effect on the level of risk management disclosure.